Pengaruh Nilai Sand Equivalent Terhadap Karakteristik Marshall Dan Durabilitas Pada Campuran AC (Asphalt Concrete) - Akbar, Safira Yaumil, Ir. Agus Riyanto, MT (2016)
In the selection of materials to be used in the manufacture of asphalt mix is not limited to the source of the material obtained, as long as the material meets the requirements in the testing material. Fine aggregate or sand from sources quarry one another will have a sand equivalent quality and value are different. So it will affect the quality of the pavement. Likewise sand that has been on the suppliers, although it has been tested equivalent sand but sand that has been collected and placed in the room is open will be contaminated with dirt or dust, so that the sand equivalent value will also change. This study aimed to determine the influance of sand equivalent value against Marshall characteristics and durability at a mix of AC (Asphalt Concrete), as well as sand equivalent value can be tolerated within the framework of reviews specification Marshall characteristics and durability. The method used in this study is an experimental method that is carried out in the Laboratory of Civil Engineering University of Muhammadiyah Surakarta . Variations used bitumen content of 5% , 5.5 % , 6 % , 6.5 % , 7 % of the total weight of the aggregate to determine the optimum bitumen content . Having obtained the optimum bitumen content it created specimens with variations of sand equivalent value of 80% , 60 % , 40 % , 20 % and then soaked for 24 hours and 48 hours . Further testing specimen Marshall and durability . Based on the results showed that the variation of sand equivalent affect the Marshall characteristics and durability of AC the mixture. At the optimum bitumen content results obtained (5.73%), clay particles contained in the fine aggregates act more as a filler, clay particles contained in the fine aggregates act more as a filler, so that the value of stability actually increases with decreasing value of sand equivalent, flow tends to rise in line with the declining value of sand equivalent, VFWA tends to decrease with increasing sand equivalent value, VIM tends to decrease with decreasing sand equivalent value, MQ tends to decrease with decreasing sand equivalent value, the greater density along with the reduced sand equivalent value. Sand equivalent value that can be tolerated is 48.31% - 80% for a 24-hour immersion and 54.86% - 80% for immersion of 48 hours. Based on the density and VIM parameter values can be seen that the sludge contained in the mixture to act more as filler. All specimens with variations of sand equivalent value indicates the value of r (a decrease in the stability index) ≤ 1%, which means that the resulting durable pavement materials.